2020
DOI: 10.1155/2020/3534042
|View full text |Cite
|
Sign up to set email alerts
|

Endocan: A Biomarker for Hepatosteatosis in Patients with Metabolic Syndrome

Abstract: Background. Nonalcoholic fatty liver disease (NAFLD) is one of the most common chronic liver diseases, which has recently been mentioned as an independent cardiovascular risk factor. Objectives. Endocan is a novel molecule of endothelial dysfunction. We aimed to evaluate the associations of serum endocan levels with the hepatic steatosis index (HSI), fatty liver index (FLI), and degrees of hepatosteatosis in patients with metabolic syndrome with NAFLD. Design and Setting. This cross-sectional prospective study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 38 publications
4
11
0
Order By: Relevance
“…Janke et al suggested that insulin resistance could increase ESM-1 expression in adipocytes although circulating levels of Endocan were actually lower and no associations were found between circulating Endocan levels and ESM-1 gene expression in adipocytes. A recent study performed by Erman et al [ 23 ] also found similar results in the adult population. In this study, the authors found lower Endocan levels in adult NAFLD patients and suggested that Endocan levels could be a predictive biomarker for metabolic syndrome.…”
Section: Resultssupporting
confidence: 71%
“…Janke et al suggested that insulin resistance could increase ESM-1 expression in adipocytes although circulating levels of Endocan were actually lower and no associations were found between circulating Endocan levels and ESM-1 gene expression in adipocytes. A recent study performed by Erman et al [ 23 ] also found similar results in the adult population. In this study, the authors found lower Endocan levels in adult NAFLD patients and suggested that Endocan levels could be a predictive biomarker for metabolic syndrome.…”
Section: Resultssupporting
confidence: 71%
“…ERP29, a chaperone protein, has been reported to be positively associated with BMI and to have a role in proinsulin secretion [39]. Of the replicated proteins, endothelial cell-specific molecule 1 (ESM1), has been reported to be low in liver steatosis in MetS patients [40] and in macroalbuminuria in T2D patients [41], both of which are in line with the negative association between ESM1 and MetS observed here. However, ESM1 was reported to be positively associated with atherosclerotic CVD [42].…”
Section: Mendelian Randomizationsupporting
confidence: 85%
“…Also, Elsheikh et al, (2014) reported that endocan (as a marker for endothelial dysfunction) was also increased in NAFLD [10] . Also, NAFLD subjects had signi cantly higher endocan levels than control group as reported with Ustyol et al, (2017) [31] .…”
Section: Discussionsupporting
confidence: 68%